2021
DOI: 10.1177/0734242x21989418
|View full text |Cite
|
Sign up to set email alerts
|

School canteens and the food waste challenge: Which public initiatives can help?

Abstract: Foodservice is estimated to produce 12% of the total food waste in Europe, and it is a major target for policies against food waste. The amount of food lost during foodservice operations has been assessed in the literature as a figure ranging from 10% to 41% of the quantity prepared in the kitchen, either as non-served food or as plate waste. In this paper, a systematization of the current initiatives against food waste in EU school foodservice is provided. This background is used as a base to discuss the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
8
0
3
Order By: Relevance
“…What happens to food waste also varies by country depending on local policy. For example, Pancino et al 25 estimated that most food waste in participating Italian schools were sent to composting or aerobic/anaerobic treatments, whereas this type of facility was not evident in the school that we studied where food waste was assigned to general waste bins intended for landfill or incineration. Lack of school policies to dispose of food waste in a compost or other recycling system is a policy barrier described by others 43 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…What happens to food waste also varies by country depending on local policy. For example, Pancino et al 25 estimated that most food waste in participating Italian schools were sent to composting or aerobic/anaerobic treatments, whereas this type of facility was not evident in the school that we studied where food waste was assigned to general waste bins intended for landfill or incineration. Lack of school policies to dispose of food waste in a compost or other recycling system is a policy barrier described by others 43 .…”
Section: Discussionmentioning
confidence: 97%
“…School food systems differ across jurisdictions, with some countries providing national school meal programmes, and others working with a combination of home packed lunches and independently run canteens, shops, and/or vending machines where students can purchase food at school. It is unsurprising, therefore, that wide heterogeneity in food waste measurement methods and estimates are reported across the literature 25,36–38 . In a European context, Malefors et al 37 aimed to establish baseline data for food waste in a variety of institutional settings, including schools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing food waste and controlling non-organic waste represent initiatives that must be implemented in school food services. Studies in different parts of the world have demonstrated that these places are major food waste generators, causing environmental, economic, and social impacts [ 101 , 102 , 103 , 104 ]. Concerning non-organic waste, a study carried out in northern Colorado, USA identified that factors such as the speed of the service line, the quality of food, the cost, and the difficulty managers have in understanding the impact of their decisions at a systemic level, affected the ability to reduce or recover these wastes [ 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reducing food waste and controlling non-organic waste represent initiatives that must be implemented in school food services. Studies in different parts of the world have demonstrated that these places are major food waste generators, causing environmental, economic, and social impacts [101, 102, 103, 104]. Concerning non-organic waste, a study carried out in northern Colorado, USA identified that factors such as the speed of the service line, the quality of food, the cost, and the difficulty managers have in understanding the impact of their decisions at a systemic level, affected the ability to reduce or recover these wastes [105].…”
Section: Discussionmentioning
confidence: 99%